Effect of seasonal variation and host genotypes on diseases of mulberry in Darjeeling - and D. DAS, S. BISWASl, S.K. DAS, N.K. DAS (Indian Phytopathology, 2012)
Five mulberry diseases, viz., Powdery mildew (Phyllactinia cory/ea), Anthracnose (Colletotrichum gloeosporioides = C. morico/a). Leaf rust (Cerotelium fici), Red rust (Aecidium mori) and Bacterial blight (Pseudomonas mori), were studied for their occurrence in four mulberry cultivars, namely, Kosen, BC 2 59, Tr10 and S146’ during three crop seasons 95-97 in the hilly region of Darjeeling. Co-efficient of disease index (CODEX) varied significantly with host genotypes, crop seasons and years for all the diseases except bacterial blight which occurred less in all mulberry varieties without any significant differences. Kosen was most tolerant to the diseases under study, however, its tolerance towards leaf rust was less than BC 2 59. The mulberry cultivar, Tr-10, was most affected by powdery mildew and leaf rust, while BC 2 59 by anthracnose and red rust. The variety like, S146’was intermediate with certain degree of susceptibility to anthracnose. Rainy season favoured the occurrence of anthracnose, while Autumn favoured leaf rust and Spring was comparatively less affected by the diseases.